PENINGKATAN AKTIVITAS BELAJAR ILMU PENGETAHUAN ALAM DENGAN METODE INKUIRI DI SEKOLAH DASAR - Syahril, Syahril; Kresnadi, Rosnita; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem of this research is about â€œ using inquiry method can improve studentâ€™s learning activities in learning science in the fifth class of elementary school of SDN 6 Sungai Pangkalan I.The Aim of this research is to describe improving students activities using inquiry method in science learningÂ  of SDN 6 Sungai Pangkalan I, in subject material â€œ sifat-sifat cahayaâ€.This research procedures include planning, implementation, observation, and reflection. This research was conducted with 3 cycles. The method using is descriptive method with form Classroom Action Research (CAR) and Collaboration. The Place of research is in SDN 6 Sungai Pangkalan I, the fifth class with the subject of research is teacher and the fifth class students. The technic of data collection that using is direct observation technic and document review. The tool of data collection are IPKG sheet I, IPKG sheet II, and the result of studentâ€™s learning activities. The result of research from lesson planning from the first cycle is 2,67, in the second cycle is 3,17, and the third cycle is 3,50. By applying the method in the assessment of the learning in the first cycle improved become 2,55, in the second cycle improved become 3,27, and cyle III improved become 3,50. The average of result studentâ€™s learning activity assessment in the first cycle is 59,72, in the second cycle is 91,67, and in the third cycle isÂ  98,6.Â  Based on the data oblained can be conclude that improving occured studentâ€™s activity in science learning with the inquiri method in the fifth class of SDN 6 Sungai Pangkalan I. Keywords: Improving, Inquiry method, Learning Activity.